Response of eichhornia crassipes (pontederiaceae) to water level fluctuations in two lakes with different connectivity in the Paraná river floodplain - Neiff, Juan José (2008)
Fil: Neiff, Juan José. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro de Ecología Aplicada del Litoral; Argentina.